O8B.5 Occupational heat exposure and cardiovascular health risks related to climate change in pacific countries. (April 2019) - Akerman, Ashley; Cotter, Jim; Kjellstrom, Tord
Abstract : Recent global analysis of current and future ambient heat conditions has shown that occupational heat exposure in Pacific countries, measured or projected as WBGT, is among the most extreme in the world. Many Pacific countries face a serious and unprecedented collision of adverse environmental, sociocultural/demographic and chronic health factors. Environmentally, high temperatures and humidity exist several months each year, reducing physical work capacity. Conservative assessments reveal annual loss of healthy work hours for a person working at 400 W metabolic rate in countries like Papua New Guinea, Kiribati, Nauru and Guam increasing from 2%–3% to 9%–18% by 2100, based on the RCP6.0 pathway for climate change. Socio-culturally, such countries have low average income levels and high reliance on primary industries, so occupational and domestic exposure to ambient heat is chronic and somewhat intractable. Health wise, such countries have among the highest burden of chronic cardiometabolic disease in the world. Diabetes is already prevalent (20%–35%), as is hypertension. Casual links between heat exposure and cardiovascular health problems is strengthening and these health problems are becoming a major threat to health in Pacific countries. A diet that is increasingly more divergent from traditional foods is one key factor, but increasing heat conditions will contribute, particularly for people working in physically intensive occupations. Obesity is also prevalent, which is relevant because it adds to heat production while concurrently reducing heat loss, thereby impairing work capacity and tolerance of humid heat. Collectively these factors compromise thermal tolerance, reduce functional capacity and contribute to cardiometabolic disease. This paper will analyse the physiological base for the heat effects on cardiovascular disease with particular reference to occupational heat exposure, and estimate the impacts of climate change in the Pacific countries as well as identify solutions to reduce the future impacts.